At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Join our platform to connect with experts ready to provide detailed answers to your questions in various areas. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Solucionemos cada una de las ecuaciones cuadráticas de forma detallada utilizando la fórmula general [tex]\( x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \)[/tex]:
### 1. [tex]\( x^2 - 5x + 6 = 0 \)[/tex]
Dado que [tex]\(a = 1\)[/tex], [tex]\(b = -5\)[/tex] y [tex]\(c = 6\)[/tex]:
1. Calcular el discriminante:
[tex]\[ \Delta = b^2 - 4ac = (-5)^2 - 4(1)(6) = 25 - 24 = 1 \][/tex]
2. Calcular las raíces usando la fórmula general:
[tex]\[ x_{1,2} = \frac{-b \pm \sqrt{\Delta}}{2a} = \frac{-(-5) \pm \sqrt{1}}{2 \cdot 1} = \frac{5 \pm 1}{2} \][/tex]
3. Encontrar las dos soluciones:
[tex]\[ x_1 = \frac{5 + 1}{2} = 3 \quad \text{y} \quad x_2 = \frac{5 - 1}{2} = 2 \][/tex]
### 2. [tex]\( x^2 - 2x + 1 = 0 \)[/tex]
Dado que [tex]\(a = 1\)[/tex], [tex]\(b = -2\)[/tex] y [tex]\(c = 1\)[/tex]:
1. Calcular el discriminante:
[tex]\[ \Delta = b^2 - 4ac = (-2)^2 - 4(1)(1) = 4 - 4 = 0 \][/tex]
2. Calcular las raíces usando la fórmula general:
[tex]\[ x_{1,2} = \frac{-b \pm \sqrt{\Delta}}{2a} = \frac{-(-2) \pm \sqrt{0}}{2 \cdot 1} = \frac{2 \pm 0}{2} \][/tex]
3. Encontrar las dos soluciones (en este caso, ambas son iguales):
[tex]\[ x_1 = x_2 = \frac{2}{2} = 1 \][/tex]
### 3. [tex]\( x^2 + x - 6 = 0 \)[/tex]
Dado que [tex]\(a = 1\)[/tex], [tex]\(b = 1\)[/tex] y [tex]\(c = -6\)[/tex]:
1. Calcular el discriminante:
[tex]\[ \Delta = b^2 - 4ac = 1^2 - 4(1)(-6) = 1 + 24 = 25 \][/tex]
2. Calcular las raíces usando la fórmula general:
[tex]\[ x_{1,2} = \frac{-b \pm \sqrt{\Delta}}{2a} = \frac{-(1) \pm \sqrt{25}}{2 \cdot 1} = \frac{-1 \pm 5}{2} \][/tex]
3. Encontrar las dos soluciones:
[tex]\[ x_1 = \frac{-1 + 5}{2} = 2 \quad \text{y} \quad x_2 = \frac{-1 - 5}{2} = -3 \][/tex]
### Resumen:
- Las raíces de la ecuación cuadrática [tex]\( x^2 - 5x + 6 = 0 \)[/tex] son [tex]\( x_1 = 3 \)[/tex] y [tex]\( x_2 = 2 \)[/tex].
- La raíz de la ecuación cuadrática [tex]\( x^2 - 2x + 1 = 0 \)[/tex] es [tex]\( x_1 = x_2 = 1 \)[/tex].
- Las raíces de la ecuación cuadrática [tex]\( x^2 + x - 6 = 0 \)[/tex] son [tex]\( x_1 = 2 \)[/tex] y [tex]\( x_2 = -3 \)[/tex].
### 1. [tex]\( x^2 - 5x + 6 = 0 \)[/tex]
Dado que [tex]\(a = 1\)[/tex], [tex]\(b = -5\)[/tex] y [tex]\(c = 6\)[/tex]:
1. Calcular el discriminante:
[tex]\[ \Delta = b^2 - 4ac = (-5)^2 - 4(1)(6) = 25 - 24 = 1 \][/tex]
2. Calcular las raíces usando la fórmula general:
[tex]\[ x_{1,2} = \frac{-b \pm \sqrt{\Delta}}{2a} = \frac{-(-5) \pm \sqrt{1}}{2 \cdot 1} = \frac{5 \pm 1}{2} \][/tex]
3. Encontrar las dos soluciones:
[tex]\[ x_1 = \frac{5 + 1}{2} = 3 \quad \text{y} \quad x_2 = \frac{5 - 1}{2} = 2 \][/tex]
### 2. [tex]\( x^2 - 2x + 1 = 0 \)[/tex]
Dado que [tex]\(a = 1\)[/tex], [tex]\(b = -2\)[/tex] y [tex]\(c = 1\)[/tex]:
1. Calcular el discriminante:
[tex]\[ \Delta = b^2 - 4ac = (-2)^2 - 4(1)(1) = 4 - 4 = 0 \][/tex]
2. Calcular las raíces usando la fórmula general:
[tex]\[ x_{1,2} = \frac{-b \pm \sqrt{\Delta}}{2a} = \frac{-(-2) \pm \sqrt{0}}{2 \cdot 1} = \frac{2 \pm 0}{2} \][/tex]
3. Encontrar las dos soluciones (en este caso, ambas son iguales):
[tex]\[ x_1 = x_2 = \frac{2}{2} = 1 \][/tex]
### 3. [tex]\( x^2 + x - 6 = 0 \)[/tex]
Dado que [tex]\(a = 1\)[/tex], [tex]\(b = 1\)[/tex] y [tex]\(c = -6\)[/tex]:
1. Calcular el discriminante:
[tex]\[ \Delta = b^2 - 4ac = 1^2 - 4(1)(-6) = 1 + 24 = 25 \][/tex]
2. Calcular las raíces usando la fórmula general:
[tex]\[ x_{1,2} = \frac{-b \pm \sqrt{\Delta}}{2a} = \frac{-(1) \pm \sqrt{25}}{2 \cdot 1} = \frac{-1 \pm 5}{2} \][/tex]
3. Encontrar las dos soluciones:
[tex]\[ x_1 = \frac{-1 + 5}{2} = 2 \quad \text{y} \quad x_2 = \frac{-1 - 5}{2} = -3 \][/tex]
### Resumen:
- Las raíces de la ecuación cuadrática [tex]\( x^2 - 5x + 6 = 0 \)[/tex] son [tex]\( x_1 = 3 \)[/tex] y [tex]\( x_2 = 2 \)[/tex].
- La raíz de la ecuación cuadrática [tex]\( x^2 - 2x + 1 = 0 \)[/tex] es [tex]\( x_1 = x_2 = 1 \)[/tex].
- Las raíces de la ecuación cuadrática [tex]\( x^2 + x - 6 = 0 \)[/tex] son [tex]\( x_1 = 2 \)[/tex] y [tex]\( x_2 = -3 \)[/tex].
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.